HUBUNGAN MOTIVASI MENGAJAR GURU DENGAN KREATIVITAS GURU PADA GURU YANG TELAH MEMILIKI SERTIFIKAT PENDIDIK PAUD SE-KOTA PEKANBARU - Sari, Diana Sari; Chairilsyah, Daviq Chairilsyah; Puspita, Enda Puspita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the variation in most of the teachers who has been certified early childhood educators as the city of Pekanbaru is already certified teachers still use the media that's it, already certified teachers can not solve the problems that occur to the students, teachers already certified still using RKH and RKM has been used in previous years and rarely to renew it, the teacher who has been certified are not able to use materials that are nearby to the learning process and still use existing APEl. The purpose of this study was to determine the relationship between motivation and creativity of teachers teaching the teacher who has been certified early childhood educators as the city of Pekanbaru. The population of this research is all the teachers who have had early childhood educator certificate as the city of Pekanbaru, amounting to 110 people. Samples used as many as 52 people. The data collection techniques used was a questionnaire that gives a statement to answer the respondent. The data analysis technique used is the analysis of statistical methods Pearson Product Moment Correlation with SPSS 16. From the results obtained are positive and significant relationship between motivation and creativity of teachers teaching in which the teacher has been certified as the city early childhood educators Pekanbaru. It can be seen from r hitung of 0.608, with p = 0.000. Therefore p <0.05 (0.000 <0.05), then Ho is rejected. In addition, the hypothesis tested also with